Zjazdy książąt śląskich w 1331 roku - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
1331 was marked by four congresses of Silesian dukes, all featuring the King of Bohemia and Poland, John of Luxembourg. The first two were closely linked to John’s planned military expedition against Ladislaus the Elbow-High of Poland. The participants of the congress held between 25 and 30 September in Wrocław included the now vassal dukes of Wrocław and Głogów. It was followed by another congress, convened between 1 and 2 October in Głogów and featuring more or less the same participants, during which John of Ścinawa renounced his rights to Głogów, which was a dower (dotalicium, Leibgedinge) of Constance, the Duke of Głogów’s widow, in favour of the Bohemian king. This created a legal basis for seizing full ducal power over the duchy and combining it with the Duchy of Wrocław he was to inherit after the death of Duke Henry VI (1335). After his failure in the war against Ladislaus the Elbow-High, John of Luxembourg again came to Wrocław and during another congress, on 19 October, featuring the same dukes, he issued several documents with privileges for the city of Wrocław and Wrocław burghers. On the same day Boleslaus of Legnica gave the king Niemcza (castle, town and district) as a pledge, for a long time in possession of the independent Duke of Świdnica, Bolko, who opposed John of Luxembourg’s policy in Poland and Silesia. The last congress of Silesian dukes that year was held on 13 December in Prague. It featured nine Silesian dukes from the House of Piast and the Bishop of Wrocław. Those absent were the Dukes of Świdnica and Jawor as well as most dukes from Upper Silesia, with the exception of Ladislaus of Bytom and Bolko of Niemodlin. The congress is confirmed by just one document, which refers to the granting of the Duchy of Legnica, to be held jointly in fee (investitura simultanea, Gesamtbelehnung), to Duke Boleslaus and his two sons in a compromise between the Polish ducal law and German feudatory law
Keywords: książęta śląscy; Wrocław; zjazdy śląskie; antecedencje; Głogów; Praga (Czechy)